The association between body composition and performance assessments with external workload metrics in Division II collegiate women's soccer - Wroblewski, S.; Morrison, T.; Anderson, K.; Murphy, A.; Bedsole, A.; Sullivan, J.; Souza, E.; Andersen, J. (The Journal of Strength and Conditioning Research, 2021)
Introduction: Aerobic fitness is known to be critical for performance in intermittent sports such as soccer. The Yo-Yo intermittent test is a soccer-specific assessment that measures an athlete's capacity to continually perform interval running and is reflective of aerobic fitness. There are many factors, including body composition that are thought to play a role in an athletes' aerobic capacity and performance. For instance, a higher percentage of body fat has been associated with a decrease in athletic performance, particularly in sports where body mass is transferred horizontally and/or vertically. Global Positioning System (GPS) and Inertial Movement Units (IMU) allow for field performance, specifically external workloads such as volume (Total Distance-TD), intensity (Meters Per Minute - M/min), and explosiveness (Total Acceleration Load-TAL) to be measured during practices and matches. Unfortunately, such technology is not available to most coaches in collegiate Division II women's soccer (D2S). Therefore, the association between body composition and on-field assessments with GPS metrics related to field performance is still unknown within D2S. Purpose: The purpose of this investigation was to determine the relationship between body composition and the Yo-Yo intermittent test with GPS field metrics. Methods: Sixteen female soccer athletes (19.6 ± 0.86 year old; 62.0 ± 9.6 kg) were monitored during the Yo-Yo endurance assessment (20-meter shuttle run with 10-second recovery) during off-season practice in Spring 2020 using GPS and IMUs (Catapult Sports Innovations). The final level completed prior to failure for each athlete was recorded and data was collected for TD, M·min-1, and TAL. Dual energy X-ray absorptiometry (DEXA) was used to measure whole and regional body composition. Additionally, a region of interest marked from the iliac crest to lateral condyle (ROI-FFM) was assessed in the lower extremities. GraphPad Prism 8.1 was used to examine the correlation between Yo-Yo level, FFM, FM, Sigma ROI-FFM, Sigma ROI-FM, and BF% with TD, M/min, and TAL utilizing a multiple variable analysis, with p < 0.05 considered statistically significant. Results: The results of the correlation analyses and their respective 95%-confidence intervals are presented in Table 1. Conclusions: Moderate negative relationships were found for FFM, FM, Sigma ROI-FFM and Sigma ROI-FM with M/min, TD, and TAL. Interestingly, we observed moderate negative relationships between FFM and Sigma ROI-FFM with M/min, plausibly due to an increase in the individual's total mass. A strong positive relationship between Yo-Yo level completed and each field metric was observed, particularly with the explosiveness measure (TAL). Practical Application: Coaches who do not have access to GPS technology may consider the correlation between the Yo-Yo intermittent test and GPS field metrics, suggesting the higher the completed level, the more intense and explosive the athlete's session.